Advanced phase chronic myeloid leukaemia (CML) in the tyrosine kinase inhibitor era – a report from the Swedish CML register. (19th August 2016) - Söderlund, Stina; Dahlén, Torsten; Sandin, Fredrik; Olsson‐Strömberg, Ulla; Creignou, Maria; Dreimane, Arta; Lübking, Anna; Markevärn, Berit; Själander, Anders; Wadenvik, Hans; Stenke, Leif; Richter, Johan; et al.
Abstract: Objectives: The primary goal in management of chronic phase (CP) chronic myeloid leukaemia (CML) is to prevent disease progression to accelerated phase (AP) or blast crisis (BC). We have evaluated progression rates in a decentralised healthcare setting and characterised patients progressing to AP/BC on TKI treatment. Methods: Using data from the Swedish CML register, we identified CP‐CML patients diagnosed 2007–2011 who progressed to AP/BC within 2 yrs from diagnosis ( n = 18) as well as patients diagnosed in advanced phase during 2007–2012 ( n = 36) from a total of 544 newly diagnosed CML cases. We evaluated baseline characteristics, progression rates, outcome and adherence to guidelines for monitoring and treatment. Results: The cumulative progression rate at 2 yrs was 4.3%. All 18 progression cases had been treated with imatinib, and six progressed within 6 months. High‐risk EUTOS score was associated to a higher risk of progression. Insufficient cytogenetic and/or molecular monitoring was found in 33%. Median survival after transformation during TKI treatment was 1.4 yrs. In those presenting with BC and AP, median survival was 1.6 yrs and not reached, respectively. Conclusion: In this population‐based setting, progression rates appear comparable to that reported from clinical trials, with similar dismal patient outcome. Improved adherence to CML guidelines may minimise the risk of disease progression.